Taxonomy of asteroids in the Cybele region from the analysis of the Sloan Digital Sky Survey colors - Gil Hutton, Ricardo Alfredo (2010)
In this paper we search for photometric data of asteroids in the outer region of the Hecuba gap in the Moving Object Catalogue of the Sloan Digital Sky Survey to find the spectrophotometric characteristics of small members of this group. We found that the correlation between size and spectral slope previously identified for Cybele asteroids is correct only for large objects (HV<12) but it is not supported by data obtained for the small ones. This result argues against the scenario suggesting that D-type objects are more fragile than P-types, favoring disruptive collisions of precursors of the first type and resulting in a larger fraction of the smaller body population being collisional fragments from a few large D-type precursors. A statistical comparison of the spectral slope histograms of Cybeles and Hildas showed that it is not possible to reject the hypothesis that both samples were obtained from the same population at a confident limit of 90%. This result could be indicative of certain homogeneity in the taxonomic distributions of the outer belt populations due to a similar original composition and/or a similar resurfacing processes of these distant bodies. Despite the intrinsic limitations of the five band photometry of the Sloan Digital Sky Survey, the analysis presented is based mainly in the detection of spectral slopes thus providing sufficient indication of the taxonomic type of these asteroids and making us confident about our conclusions.